Homicidal ideation - Vaughn, Michael G. (Routledge handbook of homicide studies, 2024)
Homicide exacts a tremendous economic and emotional toll throughout society. This chapter focuses on homicidal ideation, which is one of the major precursors to homicide. Specifically, we take a life course approach to homicidal ideation by examining early childhood, adolescent, and adulthood manifestations. We also consider the critical co-occurring psychopathology that accompanies homicidal ideation and what is known about assessment and etiology. We spend considerable chapter space to descriptively reveal through a series of case vignettes the context and interior life of homicidal ideation. We conclude by offering several approaches to advance the knowledge base on homicidal ideation.